Where does the Vein-To-Vein Transfusion Chain Start? - Sibinga, Cees Th. Smit (British Journal of Healthcare and Medical Research, 2026)
Blood transfusion has been subject of scientific thinking within health care since the 16th century based on disease expressions and therapeutic and supportive innovative ideas on how and what to transfuse from one individual to another. While exploring quite a number of mysteries were found which needed to be unraveled. History learns the difficulties to overcome and the development of the science and technology needed to safely treat and support patients in need. There is a demand for and a use of blood and blood components or products which create a need. As the transfusion of blood or blood components is a transplant practice, immunology and compatibility, cells and proteins but also materials (surface phenomena) need to be looked for and into. In the 1970s the ‘vein-to-vein transfusion chain’ came to life, interpreted and practiced starting with the source (blood donors) followed by the processing of the donated blood and ending with the patient to transfuse. Asking the question: Where does the vein-to-vein transfusion chain start?, needs a change in scientific thinking, operations and education. This despite the fact that the right quality treatment and support (pharmaceutical or other interventions) play an important role (need or requirement).